Potential Association of the Oral Microbiome with Trimethylamine N-Oxide Quantification in Mexican Patients with Myocardial Infarction - Paulina Hernández-Ruiz; Alma R. Escalona Montaño; Luis M. Amezcua-Guerra; Héctor González-Pacheco; Elena Niccolai; Amedeo Amedei; María M. Aguirre-García (Mediators of Inflammation)
Many attempts have been proposed to evaluate the linkage between the oral–gut–liver axis and the mechanisms related to the diseases’ establishment. One of them is the oral microbiota translocation into the bloodstream, liver, and gut, promoting a host dysbiosis and triggering the presence of some metabolites such as trimethylamine N-oxide (TMAO), known as a risk marker for cardiovascular disease, and especially the myocardial infarction (MI). In the present pilot study, the involvement of oral dysbiosis related to the presence of TMAO has been considered an independent component of the standard risk factors (SRs) in the development of MI, which has not been previously described in human cohorts. A positive and significant correlation of TMAO levels with Porphyromonas was identified; likewise, the increase of the genus Peptidiphaga in patients without SRs was observed. We determined that the presence of SRs does not influence the TMAO concentration in these patients. This report is the first study where the relationship between oral dysbiosis and TMAO is specified in the Mexican population. Our findings provide information on the possible contribution of the oral pathogens associated with gut dysbiosis in the development of MI, although further analysis should be performed.